The complete genome sequence of the algal symbiont Dinoroseobacter shibae: a hitchhiker's guide to life in the sea - Wagner-Döbler, Irene; Ballhausen, Britta; Berger, Martine; Brinkhoff, Thorsten; Buchholz, Ina; Bunk, Boyke; Cypionka, Heribert; Daniel, Rolf; Drepper, Thomas; Gerdts, Gunnar; Hahnke, Sarah; Han, Cliff; et al. (The ISME Journal, 2010)
Dinoroseobacter shibae DFL12 T , a member of the globally important marine Roseobacter clade, comprises symbionts of cosmopolitan marine microalgae, including toxic dinoflagellates. Its annotated 4 417 868 bp genome sequence revealed a possible advantage of this symbiosis for the algal host. D. shibae DFL12 T is able to synthesize the vitamins B 1 and B 12 for which its host is auxotrophic. Two pathways for the de novo synthesis of vitamin B 12 are present, one requiring oxygen and the other an oxygen-independent pathway. The de novo synthesis of vitamin B 12 was confirmed to be functional, and D. shibae DFL12 T was shown to provide the growth-limiting vitamins B 1 and B 12 to its dinoflagellate host. The Roseobacter clade has been considered to comprise obligate aerobic bacteria. However, D. shibae DFL12 T is able to grow anaerobically using the alternative electron acceptors nitrate and dimethylsulfoxide; it has the arginine deiminase survival fermentation pathway and a complex oxygen-dependent Fnr (fumarate and nitrate reduction) regulon. Many of these traits are shared with other members of the Roseobacter clade. D. shibae DFL12 T has five plasmids, showing examples for vertical recruitment of chromosomal genes ( thiC ) and horizontal gene transfer ( cox genes, gene cluster of 47 kb) possibly by conjugation ( vir gene cluster). The long-range (80%) synteny between two sister plasmids provides insights into the emergence of novel plasmids. D. shibae DFL12 T shows the most complex viral defense system of all Rhodobacterales sequenced to date.